العمران الإباضي في المغرب الأوسط تيهرت-سدراته- ورجلان - مدن مزاب - ليحيو سعيدة; مردف سليمة (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة إلى تسليط الضوء على الخصوصيات العمرانية التي تميز بها الإباضيون في المغرب الأوسط، من خلال تتبع نشأة وتطور أهم مراكزهم الحضرية، وهي: تيهرت، سدراتة، ورجلان، ومدن مزاب. وتسعى إلى إبراز كيف ساهمت هذه الحواضر في ترسيخ الهوية الإباضية والحفاظ على مبادئها خلصت الدراسة إلى مجموعة من النتائج المهمة، أبرزها أن العمران الإباضي في المغرب الأوسط لم يكن مجرد استجابة بيئية أو جغرافية، بل كان تعبيرًا عن منظومة عقدية واجتماعية متكاملة. فقد اتسمت المدن الإباضية بخصائص عمرانية تعكس قيم التنظيم، التكافل، والشورى، من خلال تخطيط مديني محكم، وعمارة متجانسة تخدم حاجات الجماعة وتؤمن الاستقلال الذاتي. كما أظهرت الدراسة أن هذه المدن لعبت دورًا محوريًا في حفظ الهوية الإباضية ونقلها عبر الأجيال، مما ساهم في استمرارية الوجود الإباضي رغم التغيرات السياسية والتهديدات الخارجية. "This study aims to shed light on the urban peculiarities characterized by the Ibadis in central Morocco, by tracing the origin and development of their most important urban centers, namely: tehert, sidrata, rgalan, and the cities of the mzab Valley. The study concluded a set of important results, the most prominent of which is that the Ibadi urbanism in the middle Maghreb was not just an environmental or geographical response, but was an expression of an integrated ideological and social system. The Ibadi cities were characterized by urban characteristics that reflect the values of organization, Solidarity, and Shura, through tight urban planning, and homogeneous architecture that serves the needs of the community and ensures autonomy. The study also showed that these cities played a pivotal role in preserving the Ibadi identity and transmitting it through generations, which contributed to the continuity of the Ibadi presence despite political changes and external threats. "
مذكرة ماستر قسم تاريخ تخصص تاريخ المغرب الاسلامي الوسيط
Keywords: مدن مزاب; ورجلان; سدراته; تيهرت; العمران الاباضية; Obadah; tehrat; sidrat-and two men; mzab cities